Determinasi Faktor-Faktor Keamanan E-Banking Terhadap Kepercayaan dengan Pendekatan Technology Acceptance Model - Qamaruzzaman, M. Haris; Surarso, Bayu; Suhartono, Suhartono (Universitas Diponegoro, 2011)
Safety and convenience factor is important for confidence in the use of e-banking. This study aimed to investigate the factors determination using e-banking approach to technology acceptance model, and analyze the determination of the factors the use of ebanking with the Technology Acceptance Model approach. Technology Acceptance Model (TAM) is a model used to explain the acceptance of the technology to be used by users of the technology. In the context of this study, TAM raises the safety factor and the factor of ease of use of e-banking to e-banking trust uses. This research is a field research (field research) with a quantitative approach that examines the issues being studied. Sampling method using random sampling technique as much as 100 respondents. Data collection techniques are the primary data by distributing questionnaires to the users e-banking. While the secondary data that other reports related to research. The data analysis techniques used include descriptive statistics and analysis phases of statistical regression analysis. These results prove that the safety factor has a significant and positive effect on user confidence in e-banking proven Ho is rejected and Ha accepted with a significance level of 0.001 (<0.05), while the convenience factor also has a positive and significant impact on user confidence in e-banking proven Ho is rejected and Ha accepted with a significance level of 0.000 (<0.05).Keywords: Factor Security; Ease; Confidence Use of e-banking; Technology Acceptance Model (TAM)